Towards an Inclusive Family Law - Legal-Ethical Framework Based on Autonomy and Responsibility - Hotz, Sandra (My University, 2025)
This article reflects on ways to render family law more inclusive. It elaborates on theoretical/conceptual approaches such as care ethics, responsibility ethics, and an understanding of family by agreement. In addition, I will consider the European jurisprudence on Art. 8 ECHR, which has been highly relevant to the evolution of family law for a long time. Inclusive family law can embrace various branches of family law, such as an alternative to pure kinship law within filiation law, including caring for persons as family members within the adult protection law and how to foster the autonomy of cognitively impaired persons regarding founding a family. The concept may also expand to procedural law. In this article, we will discuss examples from filiation law.
Keywords: family law | inclusion | care ethics | responsibility ethics | private ordering | families by agreement | Familienrecht | Inklusion | Pflegeethik | Verantwortungsethik | private Bestellung | Familien durch Vereinbarung